Deskripsi Karakteristik Individu Transmigran di Kabupaten Banyuasin dan Ogan Ilir Provinsi Sumatera Selatan - Malta Malta (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
Transfer of population is not only based on geographical inequality, but more important is to produce capital and human resources more optimally. the characteristics of transmigrants need attention, because this will affect the quality and performance of transmigrants at the transmigration site. The purpose of this study was to analyze the characteristics of transmigrant individuals. The study was conducted from May 2016 to January 2017. The total population was 3,537 transmigrant households. The number of the samples in this study was determined using Slovin formula. The study involved 359 respondents determined by stratified random sampling. The research data consisted of primary data and secondary data. The primary data was obtained through structured interviews, in-depth interviews, and field observations. The results of the study showed that the majority of transmigrants were of productive age (41-65 years), formal education was low, the majority of experiences were> 10 years of farming, most of the experience was following transmigration for 11-15 years, and motivation to participate in transmigration programs to obtain agricultural land.